The Effects on Corporate Social Responsibility by Shares and Teamwork Culture - Lin, Jer-Yan; Huang, Chi-Fen (Archives of Business Research, 2021)
Corporate social responsibility has become an international trend in order to maximize profits and attract the attention of scholars and practitioners. Therefore Engaging in corporate social responsibility may affect the company’s profits and cause increased costs. The social responsibility plan should determine the most necessary strategic concerns and the creating important value. Therefore Social responsibility is the key to an enterprise’s pursuit of excellence. Creating social well-being and enhancing its competitive advantage may be an important factor for the company’s future success. Promoting corporate social responsibility with shares and establishing a sustainable team-oriented culture can enhance corporate competitive advantages, create social well-being, and create value to stimulate Innovative. The empirical results showed that shares and team-oriented culture have significantly positive impact on corporate social responsibility that is further positively significant to enhance employee innovation behavior. Further finding supports that environmental altruism moderates the relationship between corporate social responsibility and shares.